Macromol. Rapid Commun. 2/2015. Issue 2 (January 2015) - Forget, Aurelien; Pique, Raphaelle‐Anne; Ahmadi, Vincent; Lüdeke, Steffen; Shastri, V. Prasad; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> Frontispiece: Polysaccharide hydrogels with tunable architecture are produced by blending β‐sheet rich carboxylated agarose (CA) with α helical native agarose (NA). Through control of the β‐sheet distribution and overall content, the mechanical properties of the resulting hydrogel can be tailored. Further details can be found in the article by A. Forget, R.‐A. Pique, V. Ahmadi, S. Ludeke, * and V. P. Shastri* on page 196. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>